2000
DOI: 10.1136/jcp.53.11.878
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic change of muscularis mucosae in early invasive colorectal adenocarcinoma

Abstract: Background-Invasive colorectal adenocarcinomas have bundles of eosinophilic spindle cells, which are regarded as myofibroblasts, in their desmoplastic stroma, some of which are continuous with the muscularis mucosa. Aim-To investigate the relation between the eosinophilic spindle cells and the muscularis mucosa based on their cytoskeletal phenotypes in early invasive colorectal adenocarcinoma. Methods-Formalin fixed, paraYn wax embedded tissues of 17 early invasive colorectal adenocarcinomas were immunostained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…It is known that the expression of proteolytic enzymes such as MMP-9 that is responsible for degrading collagen in the basement membrane is a feature of more aggressive colorectal carcinomas [21]. Degradation of the muscularis mucosae has also been observed in early colorectal cancer [22][23][24]. In view of the above evidence, it is suggested that the damage of muscularis mucosae by cancer cells contributes to the failure to diagnose ISM, especially in advanced colorectal cancer, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that the expression of proteolytic enzymes such as MMP-9 that is responsible for degrading collagen in the basement membrane is a feature of more aggressive colorectal carcinomas [21]. Degradation of the muscularis mucosae has also been observed in early colorectal cancer [22][23][24]. In view of the above evidence, it is suggested that the damage of muscularis mucosae by cancer cells contributes to the failure to diagnose ISM, especially in advanced colorectal cancer, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Normally muscularis mucosae expresses desmin and α -SMA [ 25 ] (Figures 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ), while stromal pericryptal and non-pericryptal myofibroblasts are α -SMA positive and may have focal desmin-positive immunostaining [ 25 ], especially at the crypt basis [ 26 ]. In another study, stromal cells in the early invasive area, designed as bundles of eosinophilic spindle cells on routine HE staining and partly continuous with the muscularis mucosae , showed α -SMA expression, but a loss of desmin expression [ 26 ]. The desmin immunostaining can be used for the assessment of the deepest point of invasion similar to esophageal adenocarcinoma [ 27 ].…”
Section: ⧉ Resultsmentioning
confidence: 99%
“…35,36 An anti-human desmin antibody, D33 (1:100; Dako, Glostrup, Denmark), was used as described previously. 37 …”
Section: Immunohistochemistrymentioning
confidence: 99%